2021
DOI: 10.1038/s41598-021-89773-5
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a novel low energy gamma ray shield utilizing Polycarbonate Bismuth Oxide composite

Abstract: The fabrication of different weight percentages of Polycarbonate-Bismuth Oxide composite (PC-Bi2O3), namely 0, 5, 10, 20, 30, 40, and 50 wt%, was done via the mixed-solution method. The dispersion state of the inclusions into the polymeric matrix was studied through XRD and SEM analyses. Also, TGA and DTA analyses were carried out to investigate the thermal properties of the samples. Results showed that increasing the amount of Bi2O3 into the polymer matrix shifted the glass transition temperature of the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 36 publications
5
30
0
Order By: Relevance
“…The results shown that the attenuation coefficients were increased significantly. Namely, the nanocomposite containing 50 wt % of bismuth oxide nanoparticles showed an increase of twenty-three times the attenuation coefficient compared with the pristine PC [77].…”
Section: Composites As An Approach To Enhance the Performance Of Polymers Against He-emrmentioning
confidence: 95%
“…The results shown that the attenuation coefficients were increased significantly. Namely, the nanocomposite containing 50 wt % of bismuth oxide nanoparticles showed an increase of twenty-three times the attenuation coefficient compared with the pristine PC [77].…”
Section: Composites As An Approach To Enhance the Performance Of Polymers Against He-emrmentioning
confidence: 95%
“…For these reasons, polymer composite-based materials have been the focus point of scientific interest and active multidisciplinary and industrial research groups because of their interesting properties and potential [ 20 , 21 , 22 ]. In addition, many explorers have remarkably conducted polymer composite-based radiation-absorbing substances [ 23 , 24 , 25 , 26 , 27 ]. The fact that polymers can be with ease manufactured in a coating style, characterized with an extruder, or shaped for textural parts is substantial supremacy for gamma-irradiation shielding enforcements of polymer-based compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The differences started to diminish at micro-Bi 2 O 3 loadings above 150 PHR ( Figure 7 ). This could happen due to the agglomeration of the filler in those films with a high concentration of micro-Bi 2 O 3 particles, thus producing films with a non-homogeneous dispersion of the filler [ 52 ]. Moreover, the difference in the attenuation coefficient among films at lower levels of energy is greater compared to those at higher energy levels because the photoelectric effect is predominant at low energy levels and Campton scattering increases at high energy levels [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…This could happen due to the agglomeration of the filler in those films with a high concentration of micro-Bi 2 O 3 particles, thus producing films with a non-homogeneous dispersion of the filler [ 52 ]. Moreover, the difference in the attenuation coefficient among films at lower levels of energy is greater compared to those at higher energy levels because the photoelectric effect is predominant at low energy levels and Campton scattering increases at high energy levels [ 52 ]. Therefore, the results suggest that the production of RAGs with very high concentrations of micro-Bi 2 O 3 may be impractical because filler agglomeration is expected and AE becomes progressively less additive at filler concentrations above 150 PHR.…”
Section: Resultsmentioning
confidence: 99%